SYNTHESIS AND CHARACTERIZATION OF THE HEAVY METALS; AU (III) ,Pd (II),Pt(IV) Rh(III) COMPLEXES OF S –PROPYNYL 2 –THIOBENZIMIDAZOLE - Baghdad Science Journal (مجلة بغداد للعلوم)
Complexes of Au(III) ,Pd (II) , Pt (IV ) and Rh(III) with S – propynyle -2- thiobenzimidazole (BENZA) have been prepared and characterized by IR and UV- Visible spectral methods in addition to magnetic and conductivity measurements and micro – elemental analysis (CHN).The probable structures of the new complexes have been suggested.